2007
DOI: 10.1007/s11099-007-0015-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrogen supply on photosynthetic and anatomical changes in current-year needles of Pinus koraiensis seedlings grown under two irradiances

Abstract: We investigated the responses of photon-saturated photosynthesis rate (P sat ) and its simultaneous acclimation of anatomy and nitrogen use patterns of current needles of Korean pine (Pinus koraiensis) seedlings grown under factorial combinations of two nitrogen levels and irradiances. Although N supply resulted in a significant increase of N content in needles under both irradiances, the increase of P sat tended to be suppressed only in shade (S). The significant increase of P sat in full sunlight (O) was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
24
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 33 publications
7
24
2
Order By: Relevance
“…As expected, the photosynthetic characters showed strong responses to water stress and N supply, which agreed with many previous studies (DaMatta et al 2002, Flexas et al 2006, Makoto and Koike 2007. Nevertheless, we found that water stress seemed to play the primary limitation roles in photosynthetic capacity and N supply could improve it but could not alter the declining tendency.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As expected, the photosynthetic characters showed strong responses to water stress and N supply, which agreed with many previous studies (DaMatta et al 2002, Flexas et al 2006, Makoto and Koike 2007. Nevertheless, we found that water stress seemed to play the primary limitation roles in photosynthetic capacity and N supply could improve it but could not alter the declining tendency.…”
Section: Discussionsupporting
confidence: 92%
“…There is now substantial consensus that reduced CO 2 diffusion from the atmosphere to the site of carboxylation-as a result of both stomatal closure and reduced mesophyll conductance-is the main cause of decreased photosynthesis under most water stress conditions (Chaves and Oliveira 2004, Flexas et al 2004, Ennahli and Earl 2005, Grassi and Magnani 2005. On the other hand, many studies have well documented photosynthetic responses of plants to N availability, which included significant and positive correlation between photosynthetic capacity and leaf N content, suggesting that most of the N is used for the synthesis of components in the photosynthetic apparatus (Sugiharto et al 1990, Egli and Schmid 1999, Shangguan et al 2000, DaMatta et al 2002, Makoto and Koike 2007. Furthermore, N application often brought about an increase in cell wall rigidity and osmotic adjustment (Fife andNambiar 1997, Saneoka et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Anatomical changes in needle mesophyll tissues would induce these results: a decrease in needle thickness and an increase in air space might increase the gross surface area of the mesophyll tissues. In fact, shading increased air spaces in the mesophyll tissues of an evergreen conifer (Makoto and Koike, 2007). In addition, air spaces in Pinus patula and Pinus radiata greatly affected the relationship between mesophyll tissues and light or needle N content (Niinemets et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…2). This may be due to the role of rubisco in needles as a storage organ for N, as found in several woody species (Warren and Adams, 2001;Takashima et al, 2004;Makoto and Koike, 2007). Although the metabolic cost of the investment of N in LHC proteins (including Chl) is smaller than the cost of investment in rubisco and electron transport proteins (Hikosaka and Terashima, 1995;Lambers et al, 1998), LHC proteins are more stable and harder to restore than rubisco and electron transport proteins (Makino et al, 1994;Lambers et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…A net is generally positively correlated with foliar N, which is a major component of photosynthetic-related enzymes, such as Rubisco (Cao et al 2007;Han et al 2011). N application and elevated CO 2 have synergistic effects on photosynthesis (Makoto and Koike 2007;Granath et al 2009;de Oliveira et al 2012). However, some studies have found that a low N supply can decrease or eliminate the positive Table 2 Statistical significance of single and interactive effects of population, CO 2 , and N application on physiological and biochemical parameters based on a three-way ANOVA effect of elevated CO 2 on photosynthesis (Murray et al 2000;Zhao et al 2011).…”
Section: Discussionmentioning
confidence: 99%